Respuesta :

The answer is B, 3x2=6, 6-1=5, therefore x Is 2 and y is 5

we have

[tex]y=3x-1[/tex]

we know that

If the point is an equation solution, it must satisfy the equation.

case a) [tex](4,1)[/tex]

Substitute the values of x and y in the equation

[tex]1=3*4-1[/tex]

[tex]1=12-1[/tex]

[tex]1\neq11[/tex] -------> the point is not solution of the equation

case b) [tex](2,5)[/tex]

Substitute the values of x and y in the equation

[tex]5=3*2-1[/tex]

[tex]5=6-1[/tex]

[tex]5=5[/tex] -------> the point is solution of the equation

case c) [tex](4,3)[/tex]

Substitute the values of x and y in the equation

[tex]3=3*4-1[/tex]

[tex]3=12-1[/tex]

[tex]3\neq11[/tex] -------> the point is not solution of the equation

case d) [tex](0,-3)[/tex]

Substitute the values of x and y in the equation

[tex]-3=3*0-1[/tex]

[tex]-3\neq-1[/tex] -------> the point is not solution of the equation

therefore

the answer is

The point [tex](2,5)[/tex] is solution of the equation